Myelopathy caused by nitrous oxide toxicity. - Pema, P J; Horak, H A; Wyatt, R H (American Journal of Neuroradiology, 1998)
We describe a case of myeloneuropathy resulting from nitrous oxide abuse. MR imaging of the spine revealed symmetric abnormal signal in the posterior columns of the cervical cord. Myeloneuropathy is caused by inactivation of vitamin B12 by nitrous oxide. This syndrome can also be seen in patients with borderline vitamin B12 deficiency who have recently been anesthetized with nitrous oxide.